Refleksi Keterwakilan Perempuan Dalam Parlemen Perspektif Hak Asasi Manusia - Imam Sukadi (EGALITA, 2015)
Women as nation asset who play a role in resumption process and creation of generation with high quality are require to get guarantee to accomplishment of their rights. Involvement of men and woman in political area is a part that can not be separated in democratization process. Democracy give the largest opportunity to all citizen who have fulfilled the requiremets to be able to select and selected as representative of citizen  without discrimination againt  tribe, race, religion, and gender. From some general elections which have been executed, representative of women in parliament is still in minimum number. The low of  women delegation in parliament can become indicator of the low role of woman in political party. Perempuan sebagai asset bangsa yang berperan dalam proses penerusan dan penciptaan generasi yang berkualitas perlu mendapatkan jaminan terhadap pemenuhan hak-haknya. Keterlibatan perempuan dan laki-laki di bidang politik adalah bagian tidak terpisahkan dalam proses demokratisasi. Demokrasi memberikan kesempatan seluas-luasnya kepada seluruh warga negara yang memenuhi syarat untuk dapat memilih dan dipilih sebagai wakil rakyat tanpa adanya diskriminasi terhadap suku, ras, agama, dan gender. Dari beberapa pemilu yang sudah dilaksanakan, wakil perempuan diparlemen masih sangat minim. Rendahnya keterwakilan perempuan di parlemen bisa menjadi indikator rendahnya peran perempuan di partai politik.